Ethno Cultural Specifics Brand Marketing and Social Development and Promotion Aspects - Dobryanska, Viktoria; Shynkarenko, Raisa; Muller, Maryna; Kodak., Olga (International Journal of Engineering and Technology, 2018)
â€œBrandâ€ concept modern interpretation, trade mark image characteristics, the brands role in implementing company marketing impact on consumers is considered. The article deals with confectionery products brand development and promotion based on folk traditions, examples using Sorotchinsky Fair and Opishnya toyÂ  images in figured chocolate confectionery and gift sets. Based on the study it can be concluded that allusions usage, grounded on deep psychological stereotypes, collective subconscious archetype, make the brand recognizable, understandable, desirable.